The Effect of Using Video Subtitles on Efl Students’ Listening Comprehension - Manurung, Imelda Darmayanti; Asyilah, Fara; Emelia, Tengku Winona (Holistic Science, 2024)
This study was aimed to determine whether there is the impact of using video subtitles to improve students' listening skills especially for EFL students. This experimental research was carried out in class XI SMA Negeri 2 Perbaungan for the 2022/2023 academic year. By using random sampling procedure, 60 students were chosen as the sample in this research. This study used quantitative methods and the data were taken from class XI Ipa 2 as an experimental class sample with 30 participants and class XI Ipa 1 as a control class sample with 30 participants. The test consists of multiple choice and essay. Students' pre-test and post-test scores were used to generate the data. Based on the Shapiro-Wilk tests, and SPSS 20, the two-tailed significance level for the paired sample t-test is 0.000 <0.5, it means that there is an effect of using video subtitles on students' listening comprehension. The magnitude of this effect can be seen from the average value of the Experimental Class Post-Test which increased from 73.80 to 88.56. So the results of using Video Subtitles as an interesting EFL learning media have an effect on improving students' listening skills.